Filtering of Fluctuations of the Basic Electropotential in Complex Signals of a Contactless Electrocardiogram - Evgeniy, Bogatyrev; Vladimir, Kodkin (British Journal of Healthcare and Medical Research, 2022)
The proposed article presents the results of the authors’ application of a complex electrical signal filtering algorithm developed by them, registered as a non-contact, non-invasive, abdominal ECG of a pregnant woman containing an ECG of a pregnant woman and a fetus. The previously proposed registration scheme allows you to register signals that are practically "unnoticed" by traditional ECG circuits, but it reacts very "sensitively" to changes in the basic electrical potential – the ECG baseline. It is shown that the proposed algorithm for filtering low-frequency components not only effectively eliminates the fluctuations of the baseline, but also improves the visualization of the studied cardiocomplexes necessary for the diagnosis of the condition of the pregnant woman and fetus.